A Data-Driven Fundraising Framework: Integrating Need Assessment and Social Accountability in Community-Based Islamic Philanthropy - Nurazlansyah Nurazlansyah (Institut Agama Islam Negeri Pontianak, 2025)
The increasing demand for transparency and accountability in Islamic philanthropic organizations has highlighted the limitations of conventional fundraising practices that prioritize resource mobilization without systematic beneficiary identification. This study proposes a data-driven fundraising framework that integrates multidimensional need assessment with fundraising and distribution processes to strengthen social accountability in community-based Islamic philanthropy. Employing an action research approach, the study was conducted at Lazismu Kubu Raya, Indonesia. Data were collected through field observations, structured interviews with village officials and neighborhood leaders, household surveys, beneficiary verification, and participatory observation during fundraising and aid distribution activities. The findings demonstrate that multidimensional need assessment based on housing conditions, household dependency ratio, and income stability enables the development of reliable beneficiary profiles that significantly improve targeting accuracy and reduce information asymmetry. Furthermore, integrating verified beneficiary data with micro-philanthropy fundraising through household donation boxes enhances donor confidence by increasing transparency throughout the fundraising cycle. The study also reveals that embedding aid distribution within community religious gatherings reinforces public trust and strengthens donor engagement through visible social accountability. Theoretically, this research extends the literature on Islamic philanthropy by conceptualizing fundraising as an integrated ecosystem that connects beneficiary identification, fundraising activities, and accountable distribution rather than treating these stages as independent processes. Practically, the proposed framework offers a replicable model for zakat institutions and community-based nonprofit organizations seeking to improve fundraising effectiveness, organizational legitimacy, and sustainable donor participation through evidence-based decision-making.